DEVELOPING FLASHCARD MEDIA TO IMPROVE CHILDREN’S BILINGUAL ABILITY IN KINDERGARTEN - Youhanita, Ety; Nafisah, Durrotun; Aulia Rachma, Evi; Nurdiana, Ratna; Fithria Wiji Astutik, Nur (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
Education is one of the important elements for State development. Therefore, the government is currently carrying out an educational revolution, which aims to improve the quality of education, either at the basic level or high-level learning. One of the attempts to improve the quality of education is that increasing children’s bilingual ability in kindergarten. Bilingual ability is the ability that uses two languages as a means of daily communication. The children’s bilingual ability can be developed through bilingual learning, which is taught in early childhood to develop the student’s cognitive abilities and make students recognize a more diverse foreign culture. To develop the children’s bilingual ability at the basic level, flashcard media will be developed to improve the children’s bilingual ability in the kindergarten of group B at Kamboja Kindergarten in Lamongan with the theme of transportation that is qualified to the validity criteria and practicality criteria for the kindergarten students. The test result of the flashcard media from material experts was 89.9% with very good criteria and the test result of the media experts was 76.8% with good criteria. While the individual test result was 91.2% with very good criteria, the small group test result was 90.6% with very good criteria, and the large group test result was 92.2% with very good criteria. Therefore, it implies that the development of flashcard media is suitable for students as the learning objectives and the use of flashcard media can achieve the learning objectives to improve the children’s bilingual ability in kindergarten.